A rare primary pulmonary tumor in children:Rhabdomyosarcoma - (:unkn) unknown (My University, 2010)
Lokal olarak yaygın olan tümör, 4 kür kemoterapi sonrası çekilen bilgisayarlı tomografide minimal regresyon gösterdi. Kemoterapinin 12. haftasında halen hayati yapılara yaypışıklık gösteren tümörün lokal kontrolünü sağlamak amacı ile radyoterapi uygulandı. Radyoterapiyi takiben 3 VAC (vinkristin, aktinomisin D, siklofosfamid) kürü daha verildikten sonra tümörün progresyon göstermeye devam etmesi nedeni ile tedavi sonlandırıldı. Tanıdan 9 ay sonra hasta kaybedildi. Primer pulmoner rabdomyosarkomun prognostik özellikleri tartışıldı; persistan pulmoner semoptomları ve göğüs röntgeninde anormallikleri olan çocukların ayırıcı tanısında akla gelmesi gerektiği vurgulandı

After 4 cycles of chemotherapy to treat a locally advanced tumor CT showed minimal regression of the tumor. As the locally advanced tumor was still adjacent to vital structures at the 12th week of chemotherapy, radiation therapy was given to achieve local control. The treatment was stopped after 3 additional VAC courses following radiotherapy because of continued tumor progression. The patient died nine months after the initial diagnosis. We discussed prognostic features of primary pulmonary RMS and recommend that it should be considered in the differential diagnosis of children with persistent pulmonary symptoms or chest X-ray abnormalities.
Çocukluk çağında nadir bir pulmoner tümör: Rabdomyosarkoma
Keywords: Genel ve Dahili Tıp